ACCOUNTABLE REPORTING STRATEGIES IN THE MANAGEMENT OF ZAKAT, INFAQ, AND ALMS OR SHADAQAH FUNDS AT BAZNAS SIJUNJUNG DISTRICT - MISNELI MISNELI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2022)
This research aims to describe the strategy of accountable financial reports in the management of the zakat fund at Baznas in Sijunjung District. This is a descriptive qualitative analysis research study. This research took place at Baznas in Sijunjung District. This research has nothing to do with the experimental research technique. Data were collected based on the interview in the field. Data analysis was conducted through data processing, analyzing data, and data presentation. Finally, the results of the study reveal that several strategies have been implemented to increase financial reporting accountability at Baznas Sijunjung including the Application of Accounting Based on Applicable Standards, which is guided by PSAK 109 concerning accounting for Zakat, Infaq, and Alms. Implementation of Presentation of Financial Reporting Based on Applicable Standards, namely guided by PSAK 101 concerning the Presentation of Financial Reporting of Zakat, Infaq, and Alms Organizations. Implementation of Internal Audit and Implementation of an External Audit by a Registered Public Accounting Firm (KAP).